Twin Deficits: Evidence From Portugal, Italy, Spain and Greece - Konstantinos P. Panousis; Minoas Koukouritakis (Intereconomics)
Abstract Since the mid-2000s, internal and external imbalances have increased in many EU countries. This contributed to the debate over whether government budget deficits affect current account deficits, known as twin deficits hypothesis. It implies that public debt is actually a burden for future taxpayers and thus a dangerous way for budget financing. Therefore, the fiscal measures implemented by policymakers may also affect the current account. This article tests the twin deficits hypothesis for Portugal, Italy, Spain and Greece for the period 1999–2017. The empirical analysis presented in the article finds evidence that strongly supports this hypothesis only for Italy and Greece. For Portugal and Spain, however, the evidence is quite weak.